Reliability of determining stone marten`s ( Martes Foina ) age by two different skull features - S. Peeva; E. Raichev; N. Tsandev (Trakia Journal of Sciences)
Based on skulls from Central Bulgaria, the possibilities of aging stone martens were considered and compared. Two different skull morphological criteria methods were compared to more precise method – counting of annuli in dentin. Precise aging of stone martens was only possible by counting of annuli in dentin. It is not recommended using methods by development of sagittal crest and maxillary teeth attrition separately for aging stone martens. A combination of several methods is considered to be reliable.